Dancing on the grid: electricity crises, manufacturing energy vulnerability, and jobs in South Africa - Gideon Onyewuchi Ndubuisi; Elvis Korku Avenyo; Rexford Kweku Asiama (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
South Africa's current electricity crises have worsened, placing the country on an uncertain and turbulent economic trajectory. To identify the manufacturing sub-sectors that are most vulnerable to this crises, we use the input-output matrices for the period between 1993 and 2021 to develop a sub-sector energy vulnerability index. Second, we employ the self-constructed energy vulnerability index in a flexible empirical framework to examine the effect of the electricity crises on manufacturing sector jobs in the country. We find that energy vulnerability has a high degree of heterogeneity across manufacturing sub-sectors, highlighting cross-sector differences in the level of exposure and susceptibility to the energy-related crises. Results from the empirical analysis, on the other hand, suggest that electricity crises are associated with significant job destruction, with this adverse effect severe for manufacturing sectors with higher energy vulnerability intensity. The severity of this adverse effect holds irrespective of the nature of jobs, whether formal or informal.
Keywords: L60; O14; Q40; 330; electricity crises; energy vulnerability; manufacturing; jobs; South Africa